Le roi « San Fernando » : deux nouveaux tableaux de Valdés Leal - de Moura Sobral, Luis (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1985)
Two hitherto unknown paintings by Valdés Leal (1622-1690), both in Spanish private collections, are published and discussed. A Saint Ferdinand Conqueror of Jaén, of 1673-75 (Fig. 3), is a preparatory oil-sketch for the large canvas in the cathedral of Jaén (Fig. 1). It represents the Spanish king Ferdinand III (1198-1252), hero of the ‘reconquista,’ whose canonization in 1671 was celebrated in the Seville cathedral by a series of ceremonies and feasts. Valdés Leal was deeply involved with these ceremonies, together with his friend the sculplor Pedro Roldán (1624-1700), generally credited with the creation of the typology of the new saint. A drawing by Valdés Leal in the Kunsthalle, Hamburg (Fig. 2), is certainly related to the Jaén commission as well. The second previously unpublished painting, a Saint Ferdinand (Fig. 4), is here identified as the one in possession of Leon y Ledesma, Canon of the Sevillian cathedral, a contemporary of Valdés Leal. The painting was mentioned in the inventory of León y Ledesma’s belongings (Gestoso, 1916).